VD_FINDINFO Décision / 2014 / 79 vom 31. Januar 2014 - VD Tribunal cantonal (2014)
CRÉDIBILITÉ, CONFRONTATION, ADMINISTRATION DES PREUVES, DROIT D'ÊTRE ENTENDU | 139 CPP (CH), 147 CPP (CH), 154 al. 4 CPP (CH), 394 let. b CPP (CH)